Ragam Hias Gaya Tionghoa sebagai Indentitas Bangunan Candra Naya - Harbyantinna, Aprilia Lutfiah Dwireza; Raudhoh, Rara Siti; Andrianawati, Aida (Waca Cipta Ruang, 2022)
​​ Chinese cultural acculturation happens in several cities in Indonesia through archipelago trade flow. Chinese culture spread into several aspects, starting from language, arts, foods, fashion, religion, and also architecture. House and pagoda were a building that mostly applied Chinese Architecture that have a lot of ornament decorations with their special color in it. Geometry, animal pattern, flower pattern, nature pattern,and legend are the most used ornament decorations it also has a certain meaning, it depends on Chinese belief. One of the remaining buildings that applied Chinese Architecture in Jakarta was Candra Naya. Candra Naya was a house on Chinese Major that has had restoration anis d now used as a cultural heritage building. The site of Candra Naya is less known by the local people, so the existing wealth of the building was known internally only. This research was conducted to find out the ornament decorations influence and acculturation of Chicultureturas identity on Candra Naya. This research method uses visual analysis with a qualitative approach. By collecting data from literatures, observation , and interview with Candra Naya’s caretaker. Results of the research show that ornaments decoration of Chinese architecture influence the Candra Naya building as its identity and can be a new source the for the reservation of cultural heritage in Indonesia. Keywords: Acculturation, Chandra Naya Building, Chinese, Color, Decorations